Respostas
respondido por:
0
(n+1)!/(n-1)!= 12 (utilizando propriedades dos fatoriais )
(n+1).(n).(n-1)!/(n-1)! = 12
(n+1).(n) = 12
n² + n = 12
n² + n - 12 = 0 (equação do segundo grau )
Δ = 1 + 48
Δ = 49
n = -1 +-√49/2
n = -1 +-7/2 ( como é fatoriais descartamos o - 7)
n = -1 + 7/2
n = 6/2
n = 3 ok
(n+1).(n).(n-1)!/(n-1)! = 12
(n+1).(n) = 12
n² + n = 12
n² + n - 12 = 0 (equação do segundo grau )
Δ = 1 + 48
Δ = 49
n = -1 +-√49/2
n = -1 +-7/2 ( como é fatoriais descartamos o - 7)
n = -1 + 7/2
n = 6/2
n = 3 ok
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás